Practical PowerPivot & DAX formulas for Excel 2010 [ - Tennick, Art (McGraw-Hill, 2011)
"Develop effective business intelligence (BI) solutions and drive faster, better decision making across your enterprise with help from a veteran database consultant and trainer. Through clear explanations, screenshots, and examples, Practical PowerPivot & DAX Formulas for Excel' 2010 shows you how to extract actionable insights from vast amounts of corporate data. More than 250 downloadable DAX formulas plus valuable appendices covering SQL, MDX, and DMX query design are included in this hands-on guide"-- Provided by publisher